Post-Colonial Reading of the Politics of International Donor Support in Nigeria - Yadima, Gaius Jeff (International Journal of Education, Culture, and Society, 2025)
This study critically examines the politics of international donor support in Nigeria through a post-colonial lens, exploring its implications for national sovereignty, economic development, and governance. The research investigates how foreign aid, while often framed as a development tool, perpetuates economic dependency and policy subjugation. Utilising dependency theory and post-colonial theory, the study evaluates the extent to which donor interventions influence Nigeria’s policy autonomy. This study adopts a qualitative approach, utilising secondary data from peer-reviewed journals, books, online materials and case studies. The findings indicate that while international aid has contributed significantly to healthcare, education, and infrastructure development, its effectiveness is often undermined by corruption, weak institutional frameworks, and external policy conditions imposed by donor agencies. Moreover, the study highlights the neo-colonial undertones of donor support, where funding is frequently tied to structural adjustments that limit Nigeria’s self-determination. The study concludes that achieving sustainable development in Nigeria requires a strategic shift towards economic diversification, enhanced transparency in aid management, and increased local ownership of development initiatives. Recommendations include strengthening governance institutions, reducing donor dependency, and fostering domestic revenue generation to ensure long-term economic resilience.